Role of Streptococcus pneumoniae extracellular glycosidases in immune evasion - Mathew, Bijina J.; Gupta, Priyal; Naaz, Tabassum; Rai, Rupal; Gupta, Sudheer; Gupta, Sudipti; Chaurasiya, Shivendra K.; Purwar, Shashank; Biswas, Debasis; Vyas, Ashish Kumar; Singh, Anirudh K. (Frontiers in Cellular and Infection Microbiology, 2023)
Streptococcus pneumoniae (pneumococcus) typically colonizes the human upper airway asymptomatically but upon reaching other sites of the host body can cause an array of diseases such as pneumonia, bacteremia, otitis media, and meningitis. Be it colonization or progression to disease state, pneumococcus faces multiple challenges posed by host immunity ranging from complement mediated killing to inflammation driven recruitment of bactericidal cells for the containment of the pathogen. Pneumococcus has evolved several mechanisms to evade the host inflicted immune attack. The major pneumococcal virulence factor, the polysaccharide capsule helps protect the bacteria from complement mediated opsonophagocytic killing. Another important group of pneumococcal proteins which help bacteria to establish and thrive in the host environment is surface associated glycosidases. These enzymes can hydrolyze host glycans on glycoproteins, glycolipids, and glycosaminoglycans and consequently help bacteria acquire carbohydrates for growth. Many of these glycosidases directly or indirectly facilitate bacterial adherence and are known to modulate the function of host defense/immune proteins likely by removing glycans and thereby affecting their stability and/or function. Furthermore, these enzymes are known to contribute the formation of biofilms, the bacterial communities inherently resilient to antimicrobials and host immune attack. In this review, we summarize the role of these enzymes in host immune evasion.